The effect of dietary crude protein substitution as protected soybean meal on pregnant and lactating ewes’ performance - I-W Mathius; D Yulistiani; W Puastuti (Jurnal Ilmu Ternak dan Veteriner, 2002)
Production respons was related to rumen undegradable protein feeding. Twenty-six local late pregnant ewes are penned individually and allocated to four dietary treatment groups of feed supplement, containing different amount of protected soybean meal and provided 0% (R1), 10% (R2) 20% (R3) and 40% (R4) crude protein of feed supplement respectively. Diets were fed until the first 8-week of lactation phase. Results showed that the mean of total dry matter intake (DMI) during late pregnancy was 3,42% of body weight (BW). Dietary treatments of protected-protein tended to increase daily mean intake of dry matter (P>0.05), ie. 76.9; 77.25; 77.49 and 78.81 g/kg BW 0.75 for R0, R1, R2 and R3 respectively. A similar trend was noted in daily intake of crude protein with the mean of 9.75; 10.31; 10,75 and 12.1 g/kg BW0.75 (for R0, R1, R2 and R3 respectively) and were not different significantly (P>0.05) among dietary treatments. Increasing the amount of protected-protein in the ration influenced (P<0.05) the daily live weight gain (ADG) of ewes during the late phase of gestation which was 104.4, 99.4, 120.8 and 148.14 for R0, R1, R2 and R3 respectively. Feed efficiency (DMI/ADG) improved as substitution of protected-protein increased. The total birth weight of lambs (g/ewe) was not significantly different (P>0.05), by increasing level of protected-protein in the ration, averaging 3.2 kg/ewe. Increasing protected-protein, increased (P<0.05) the daily gain (g/ewe) of lambs during the first 8-week of lactation, and it was 127, 131, 165 and 211 g/ewe/d for R0, R1, R2 and R3 respectively. Consequently, the weaned weight at 8- week of ages increased significantly different (P<0.05) as the amount of protected-protein in the diet increased.   Key words: Banana latex, protected-protein, ewes production